FATHER’S CHILDHOOD EXPERIENCE, DEPRESSION AND ANXIETY SYMPTOMS IN PERINATAL PERIOD AND THEIR INVOLVEMENT IN INFANT CARE - Miltuze, Anika; Vedeņejeva, Veronika (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The aim of this research is to make a longitudinal study of the associations between men’s childhood experience and their involvement in infant care, also, whereas psychological state of a future father during child’s perinatal period affect their involvement in infant care. The research consists of two stages. In the first stage, 43 respondents took part – men between the ages of 23 and 40, who, at the moment of the research, for the first time had prepared themselves to become fathers and their children’s mothers were on the last trimester of pregnancy. In the second stage of the research (after childbirth) from 43 respondents 27 young fathers gave their feedback. Fathers completed the Traumatic Antecendents Questionnaire (Herman, &Van der Kolk, 1989), The Gotland Male Depression Scale (Zierau, et al., 2002), The State-Trait Anxiety Inventory (Spielberger, Gorsuch, Lushene, Vagg & Jacobs, 1983), as well as The Newborn Care Involvement Self-Assessment Inventory which was made for the present research. Results shoved that father’s involvement in infant care is not associated with their childhood experience, but is positively predicted by the state anxiety and negatively – by the trait anxiety. Statistically significant differences between prenatal and postnatal measurements exist only for the state of anxiety.